Tomb of Gubah Kh Sulaiman who spread Islamic knowledge on earth in Sedulang Setudung - sustia ningsih; Hudaidah, Hudaidah; Hidayatullah, Muhammad Bagas; Bilal, Bilal; Yuliatin, Yuliatin (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
In general, Islam came to the archipelago because it was brought by traders from various countries who had embraced Islam first. Like the Islamic heritage belonging to KH Sulaiman Bin Abdurrahman Delamat where he came to Pangkalan Balai to spread Islam and left traces of heritage that became cultural heritage and many pilgrims came to pay Nazar and he was a hero of independence in Sumatra. The author uses a qualitative research method that is produced from interviews and direct documentation by conducting observations at the location of the tomb located on Jalan Kelurahan Kendodong Raye,Banyuasine, Banyuasin III District, Banyuasin Regency 111. There are two results that will be discussed by the researcher, namely the first background of KH Sulaiman bin KH Abdurrahman Delamat and the spreader of Islamic religious knowledge in Pangkalan Balai